STRATEGIC MODELING OF BUSINESS CONTINUITY MANAGEMENT (BCM) SYSTEMS IN THE DIGITAL ECONOMY AND THE IMPACT ON ENTERPRISE SUSTAINABILITY (Universal International Scientific Journal, 2026)
This article provides a detailed analysis of the theoretical foundations of Business Continuity Management (BCM) systems, the experience of crisis management in small and medium-sized enterprises, and strategic modeling mechanisms. The study is based on a BCM model integrated with risk assessment, Business Impact Analysis (BIA), RTO and RPO indicators, post-crisis costs, and digital infrastructure. An integrated approach allows you to increase the stability of the enterprise and reduce financial losses.
Keywords: BCM; business continuity; risk management